YouTube-Based Pronunciation Instruction Throught Pronunciation With Emma: Enhancing Students' Mastery of English Diphthong Sounds - Whana Sri Ayu Ningtias; Maemuna Muhayyang; Haryanto Haryanto (CV. Ulil Albab Corp, 2026)
The study investigated whether the Pronunciation with Emma YouTube channel could have positive effects on junior secondary students’ pronunciation of English diphthongs. A pre-experimental one-group pre-test and post-test design was used. The participants were 9th grade students of Class IX.K at SMP Negeri 3 Sungguminasa. The data were obtained from a pronunciation reading test made up of 40 words using eight diphthongs in English. The pre-test was prepared and used to assess students’ pronunciation achievement (AO1) at first, then a post-test was conducted after 4 treatment sessions using selected videos from Pronunciation with Emma channel. Quantitative data were also interpreted with descriptive statistics by the paired-sample t-test. It is established that students’ mean score increased as from 50.33 in the pretest to 73.93 in the post-test. The paired-sample t-test result was significant, p < .001, which suggests this improvement was significant in the outcomes following the intervention. Improvements were also observed for all eight diphthong sounds. Since pronunciation with Emma can give a useful audio-visual model, articulation support, and repetition effect to EFL learners as additional media in practice, it is a pedagogical view to aiding students in their development of English diphthong pronunciation performance.